On the Development of a Real-Time Multi-sensor Activity Recognition System - Banos, Oresti; Damas, Miguel; Guillen, Alberto; Herrera, Luis-Javier; Pomares, Hector; Rojas, Ignacio; Villalonga, Claudia; Lee, Sungyoung (Ambient Assisted Living. ICT-based Solutions in Real Life Situations, 2015)
There exist multiple activity recognition solutions offering good results under controlled conditions. However, little attention has been given to the development of functional systems operating in realistic settings. In that vein, this work aims at presenting the complete process for the design, implementation and evaluation of a real-time activity recognition system. The proposed recognition system consists of three wearable inertial sensors used to register the user body motion, and a mobile application to collect and process the sensory data for the recognition of the user activity. The system not only shows good recognition capabilities after offline evaluation but also after analysis at runtime. In view of the obtained results, this system may serve for the recognition of some of the most frequent daily physical activities.